TINGKAT KESADARAN MASYARAKAT UNTUK MEMBAYAR PAJAK DAERAH DALAM MENDUKUNG PEMBANGUNAN (Studi di Wilayah Pemerintahan Kota Serang) - Djasuro Surya; Dede Hamdan; Fathul Muin (FEB Universitas Sultan Ageng Tirtayasa, 2019)
Regional tax is an effort for sustainable regional development. Serang City is a region that has considerable regional tax potential. This study aims to analyze the level of awareness of the people of Serang city to pay Regional Taxes in order to support urban development. The results showed that the awareness of the people of Serang in paying regional original taxes (PAD) has increased from 2010 to 2017, however, the level of independence of the city of Serang has not been achieved this is evident from the relatively high level of dependence on the central government and the contribution of PAD in 2017 has not touched 20% (to be exact only 17.98%), while the previous year was all below 2017. To optimize PAD there were several suggestions that were submitted to the Serang city government, namely: detailed socialization to the entire community about the importance of regional taxes; Similar or fair treatment of all entities that do business; Providing free accounting software to facilitate paying for taxpayers; More real realization of development is needed by the city government.